PD-L1 Expression in Colorectal Carcinoma: Immunohistochemical Study - Gupta, Mehak; Manjari, Mridu; Kaur, Harjot (Annals of Pathology and Laboratory Medicine, 2020)
Background : Colorectal carcinoma is the most common type of GIT malignancy which is a multifactorial process with etiology encompassing genetic factors, environmental exposures and inflammatory conditions of the digestive tract. Method: 40 histologically proven cases of colorectal carcinoma were subjected for IHC expression of PD-L1 using Biocare kit. PD-L1 was taken positive as yellow to brown particles in membrane, cytoplasm or both. It was graded depending upon staining intensity and percentage of the cells and scoring was done by multiplying both and â‰¥ 3 was taken as positive score. Result : Most of the cases were in 6th and 7th decade of life (62.5%) with M:F ratio being 1.4:1. Most common site involved was rectum. Histologically 29 cases were conventional adenocarcinoma with rest being mucinous and mucin secreting type and most of them being moderately differentiated (70%). On immunohistochemistry, PD-L1 expression was seen in 20 cases with moderate and strong intensity. But PD-L1 score was positive in 14 cases (35%). TIL was positive in 57.5% of the cases. Statistically there was significant correlation between histological type of tumor with PD-L1 (p value=0.03) and TIL (p value=0.017). Although PD-L1 positivity was insignificant with histological differentiation (p value=0.65) but TIL was significant (p value=0.03). Conclusion : PD-L1 expression is relevant to the prognosis as well as for further CRC therapies whereas the TIL cell positivity has become an independent predictor of patients survival.